TINJAUAN FIQIF MUAMALAH ISLAM TERHADAP SISTEM GADUH KAMBING DI DESA BANYUANYAR KEC. KALIBARU - Nurul Hidayah; Balya Hidayat (NATUJA: Jurnal Ekonomi Syariah, 2022)
Not all residents of Banyuanyar village kec. Kalibaru has the capital to buy goats and breed, there are some goat breeders who are keepers of other people's goats for a profit. This system has been around for a long time. Each goat raised by breeders from other people to the system for yields is generally observed from the offspring produced. Goat maintenance work that is able to share the livelihood of its keeper. This type of research is field research with a qualitative approach, procedures for collecting information through observation, interviews and documentation. And analysis using descriptive analysis procedures. The results of the research show: A system for results in raising goats for Muslim residents in Banyuanyar Village, sub-district. Kalibaru is tried to comply with the common convention that was tried at the beginning of the agreement, the average system to be tested is 60%: 40% or 50%: 50% (between investors and custodians) investors share the capital for the purchase of goats and the custodian is responsible for keeping the goats until they are sold. For the results that are tried after the goats are sold, from this result it can increase welfare with an additional income of Rp. 500. 000, - up to Rp. 750,000 of the goats sold, so as to increase people's income and reduce poverty. Economic activities carried out for profit are stated in a mudharabah contract in which one party becomes the investor and one party becomes the executor with mutually agreed results and does not harm either party. Second, the profit-sharing system in raising goats for the Muslim community in Banyuanyar Village, Kec. Kalibaru in the Islamic economic perspective includes harmony between individual interests and the interests of the community who get mutual benefits which gives birth to the principle of social justice in the context of creating prosperity or reducing poverty with income derived from the profit sharing, economic activities carried out in profit sharing are included in the mudharabah contract where one party becomes the investor and one party becomes the executor with a mutually agreed profit sharing and does not harm either party.